1999
DOI: 10.1002/(sici)1521-3951(199910)215:2<1083::aid-pssb1083>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Internal Stresses in Electronic Pairing of Layered Superconductors

Abstract: We consider an extended electronic model for superconducting ceramics. The driving force for superconductivity in a single band model is the nondiagonal Coulomb interaction (correlated hopping), Δt = (ii| 1/r |ji). This driving force is supplemented by the quantum expression describing the internal local deformation of the Cu–O layers. The BCS equation is solved numerically for a single band model. It is shown that a physically reasonable set of hole‐deformation coupling constants will lower significantly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This effect could possibly explain the existence of the AF at the almost full subband in the high temperature superconductors. There is one limitation in here; that these are s-wave s 0 + s x 2 +y 2 superconductors, since the assisted hopping contributes only to the superconductivity of this type of symmetry (see [10] for more detailed analysis of this problem).…”
Section: Numerical Examplesmentioning
confidence: 99%
“…This effect could possibly explain the existence of the AF at the almost full subband in the high temperature superconductors. There is one limitation in here; that these are s-wave s 0 + s x 2 +y 2 superconductors, since the assisted hopping contributes only to the superconductivity of this type of symmetry (see [10] for more detailed analysis of this problem).…”
Section: Numerical Examplesmentioning
confidence: 99%
“…The kinetic interactions give rise to both of these mechanisms in creating the ferromagnetic state. They were also used in describing the superconductivity [23,24,25,26,27,28,29]. Hirsch [23,24] and Micnas [26] have shown that the interaction ∆t leads to s-wave singlet superconductivity in a less then half-filled band system.…”
Section: Introductionmentioning
confidence: 99%